‘Spoken Communication Skills taught at English Language Institutes as a second language’ - Raja, Farhan Uddin (Journal of Research in Humanities, 2023)
This study aims to explore the various methods used to accomplish oral communication competence in English language institutes. The study can prove to be a valuable contribution in assessing and improving the methods and techniques used in the conversational classes conducted at language institutes. The focus of this research is to highlight the different types of activities and the processes involved in teaching verbal communication skills at English language institutes. Communication has always been quintessential for verbal transactions and English more specifically has become an integral part for social and professional development. As these institutes are basically aiming at enabling people to converse in the target language effectively, therefore the objective is to discover the different methods and techniques employed by the institutes, and then through the analysis of those methods finding the possibilities of improvement in the learning process and recommending ways to revise them. This research comprises the observation and analysis of the activities used in conversational classes with the fuller description of the processes involved. It also comprises the description of the factors deficient in the selection of the activities for the successful acquisition of oral communication along with the recommendations for the betterment.